Production of Mono-and Diacylglycerols from the Esterification of Palm Oil Fatty Acid Distillate Catalyzed by Immobilized Rice Bran Lipase in a Packed Bed Reactor - Chong, Fui Chin (2006)
Rice bran lipase (RBL) was preserved and immobilized onto the rice bran by treating with phosphate buffer. The activities of RBL were determined by the esterification assay using oleic acid and glycerol (molar ratio of 2:1) as substrate and hexane as reaction medium. The effects of immobilization on the stability of RBL at higher temperature and in organic solvent were examined. The untreated and immobilized RBL exhibited the highest esterification activity of 1.25 and 3.55 U/g at 45 and 65ºC respectively. At 75°C, the untreated RBL completely lost its esterification activity whereas the immobilized lipase still posses 48% esterification activity. The immobilized RBL retained a relative esterification activity above 80% after 16 hours of incubation in hexane compared to only 50% for that of the untreated RBL. As a result, the immobilized RBL was selected for the subsequent experiment of esterification of free fatty acid from palm oil fatty acid distillate (PFAD) with glycerol in hexane to produce acylglycerols (MAG and DAG). The esterification mixture: PFAD (20 g), glycerol (3.35 g) (as glycerol/fatty acid ratio 1:2 molar), hexane (40 g), silica gel (10 g) and immobilized RBL (100 g) was well mixed by shaking at 100 rpm. The maximum degree of esterification, 69.8%, was achieved at 65ºC after 2 hours reaction. A packed bed reactor (PBR) was designed and constructed based on the esterification result obtained from the shaked flask experiment. The developed PBR in this study had an efficient heating system, and a water removal system to remove the reaction water from the esterification reaction. The material of construction of the jacketed thermostated packed bed vessel is stainless steel (SUS 304), which is resistant to corrosion and non-toxic to the process enzyme. The reactor is mobile and easy to operate, where the loading and unloading process of the immobilized enzyme is simple to carry out. The result of performance test showed that the heating system installed is efficient to control the temperature in the packed enzyme bed. The intensified esterification reaction was operated by circulating of 10 l reaction mixtures (PFAD and glycerol) in hexane through a packed bed column filled with 10 kg of immobilized RBL. The process parameters that can influence the performance of PBR such as reaction time, reaction temperature and type of water removal agent were investigated. The esterification reaction in PBR was optimum at reaction temperature of 65ºC and the use of silica gels (1 kg) as water removal agents. The product of esterification (MAG and DAG) was qualitatively identified by rapid thin-layer chromatography (TLC) method. The performance of PBR was generally better than that in shaked flask in terms of maximum degree of esterification and reaction time required.The intensified esterification of PFAD and glycerol catalysed by immobilized RBL in the self fabricated PBR had resulted a comparable 61% in maximum degree of esterification and 0.5 h shorter in reaction time than that in shaked flask, at reaction temperature of 65ºC and the use of silica gels (1 kg) as water removal agent. Since both rice bran and PFAD are agroindustrial residues and abundantly available in Malaysia, the successful of application of RBL as biocatalyst for the esterification of FFA from PFAD with glycerol in hexane to produce MAG and DAG has a very important impact both on the economy and environmental aspect of rice and palm oil process industry.